Appreciative Inquiry Handbook: The first in a series of AI workbooks for Leaders of Change - Cooperrider, David L.; Stavros, Jaqueline M.; Whitney, Diana (San Francisco Berrett-Koehler Publishers, 2003)
"Appreciative Inquiry Handbook explains in-depth what AI is and how it works, and includes stories of AI interventions and classic articles, sample project plans, interview guidelines, participant worksheets, a list of resources, a glossary of terms, and more.